FRAMING ANALYSIS ON CUSTOMS REGARDING THE JAPAN TROPHY - Daniel Susilo; Carlo Magno T. Mendoza (Sean Institute, 2023)
In the digital age, news site is no longer conventional and hard-printed newspaper but already presented in the form of online news. With the existence of social media and online news, citizen journalism is born among the people who contributes to distributing perceptions between people. People who discover certain issues either through news or social media will be able to choose on their own about what to believe or what to talk that later influenced their daily’s option after obtaining certain awareness. That includes the topic about Customs and the Japan Trophy, which is news from the citizen journalism product, a viral titled news distributed among the people and caused critics directed towards Customs staff and regulations. With the Frame Aanalysis, the complex and dynamic method helps Author and audience discover about the difference of cover both sides and neutrality in the news.